Entrustable Professional Activities in Orthopaedics. Issue 2 (April 2021) - Watson, Adam; Leroux, Timothy; Ogilvie-Harris, Darrell; Nousiainen, Markku; Ferguson, Peter C.; Murnahan, Lucas; Dwyer, Tim
Abstract : Background: An entrustable professional activity (EPA) is defined as a core task of a specialty that is entrusted to a trainee once sufficient competence has been reached. A group of EPAs reflects the activities that clinicians commonly do on a day-to-day basis. Lists of EPAs have been created for most medical subspecialties, but not orthopaedic surgery. The aim of this study was to create a peer-reviewed list of essential EPAs that a resident must perform independently before completing orthopaedic residency training. Methods: A focus group of 7 orthopaedic surgeons from the University of Toronto developed a comprehensive list of 285 EPAs. For each subspecialty group, the opinions of at least 15 academic and nonacademic surgeons, as well as subspecialty-trained and non–subspecialty-trained surgeons, were used. The modified Delphi method was used to rank EPAs on a five-point scale from not important to mandatory for a resident to competent before exiting training. Two Delphi rounds were used, using a threshold of >50% of surgeons considering the EPA as mandatory before being considered for the next round. A final list of EPAs was ratified using the focus group of academic surgeons involved in the study. Results: Seventy-five (75) of 107 (70%) surgeons invited responded to the survey. Nearly half (129) of the 285 EPAs were discarded after the first round of Delphi. A further 118 EPAs were discarded after the second Delphi round, leaving 49 final EPAs, across 9 subspecialties in orthopaedic surgery. Conclusions: Expert consensus was used to create a list of EPAs considered mandatory for completion of resident training in orthopaedics in our province. The final 49 peer-reviewed EPAs will be a valuable benchmark in curriculum design and assessment in orthopaedic surgery in the competency-based era for other programs.